Implementation of Educational Supervision during the Pandemic Period at Middle School in Kebumen District - Vira Ayuningrum; Siti Alimah; Noor Aini Habibah (Journal of Innovative Science Education, 2023)
This study aims to describe the implementation of the principal's academic supervision in Kebumen District Middle School which is carried out by the school principal. The approach used is a qualitative approach with a case study design. The collection of data used in this study was carried out through interviews, observation and documentation. Data analysis, namely the steps of data reduction, data presentation, and drawing conclusions. The results of the study show that the implementation of school principals' academic supervision during the pandemic: (1) Efforts by school principals to prepare online learning, by motivating teachers; (2) the principal's academic supervision program, namely individual supervision; (3) The school principal's academic supervision strategy, namely individual supervision through scheduled supervision activities in odd and even semesters; (4) Supporting school principals' academic supervision, namely school principals carrying out academic supervision aimed at increasing teacher motivation as well as providing adequate facilities and infrastructure to carry out supervision during the pandemic.